Analysis of Possibility of the Combination of Affine Cipher Algorithm with One Time Pad Cipher Using the Three-Pass Protocol Method in Text Security. (August 2019) - Ridho, Abdurrahman; Dewi, Ananda Mutya; Siregar, Rosma; Zarlis, Muhammad; Hartama, Dedy
Abstract: The use of the Three-Pass Protocol method in exchanging secret text messages is one effective method because the two interested parties do not need to use a single key to open the message sent. But there is a possibility that the message cannot be described because the cipher used is not suitable. The purpose of this study is to show whether the Affine Cipher Algorithm with One Time Pad Cipher using the Three-Pass Protocol method can be used to encrypt and decryption the text message.